The Incidence of Acute Rheumatic Fever in a Suburban Area of Los Angeles: A Ten-Year Study - Odio, Alberto (1986)
The incidence of in-hospital cases of acute rheumatic fever in residents of the San Fernando Valley section of Los Angeles (population 1,096,000) from 1971 through 1980 was 0.21 per 100,000 population for all ages and 0.63 per 100,000 for 5 to 17 year olds, both among the lowest ever reported in the world literature. Nevertheless, minority group patients had five times the risk of a white patient for acute rheumatic fever developing and a greater than 20-fold increase in the risk for the development of acute rheumatic fever with carditis. Unexpectedly, a low 30% of cases (8/27) had carditis either alone or with other major criteria, while a high 59% (16/27) had polyarthritis as the only major manifestation. This suggests the possibility of false-positive cases based on polyarthritis as the only major manifestation, and that an incidence of acute rheumatic fever may have been reached that is so low that “background” cases are a significant proportion of all cases.